1995
DOI: 10.1080/00288233.1995.9513102
|View full text |Cite
|
Sign up to set email alerts
|

Development of subterranean clover(Trifolium subterraneumL.) genotypes for New Zealand pastures 2. Wairakei persistence evaluation

Abstract: A 3-year trial to evaluate the persistence of a number of selected subterranean clover (Trifolium subterraneum L.) lines and cultivars was carried out in grazed pastures in hill country of the central North Island, New Zealand. Seedlings were transplanted into existing swards on an easy (10-15° slope) contoured paddock. Spring cover, summer/autumn seedling emergence, and winter plant populations were measured, focussing on annual regeneration of the lines. Important factors in the success of subterranean clove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Buried seed, measured in March, and hence regarded as hard seed, was 21-69% of the total. An evaluation on drier pumice hill country (Dodd et al 1995b) gave an almost identical result, but with the addition of 'Karridale' to the top performing lines.…”
Section: Tablementioning
confidence: 85%
“…Buried seed, measured in March, and hence regarded as hard seed, was 21-69% of the total. An evaluation on drier pumice hill country (Dodd et al 1995b) gave an almost identical result, but with the addition of 'Karridale' to the top performing lines.…”
Section: Tablementioning
confidence: 85%
“…Values were within ranges found for other clover species from 150 to 300°Cd (Lonati et al, 2009; Moot et al, 2003). This implies that management of subterranean clover cultivars at these early vegetative stages should consider other plant characteristics such as morphological traits (for example leaf size), growth habit (Dodd, Sheath, & Richardson, 1995), phytotoxicity (Lewis, 2017) and adaptability (Ghamkhar et al, 2012; Teixeira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to red clover, T. subterraneum has high levels of formononetin which is generally selected against early in the breeding programme ( Nicholas et al, 1981 ). Trials across New Zealand have been evaluated to select T. subterraneum lines that have improved persistence and dry matter production ( Dodd et al, 1995a , b , c ). Recent studies have identified Australian cultivars that are best adapted to New Zealand dryland pastoral systems ( Lucas et al, 2015 ; Olykan et al, 2018 ).…”
Section: History Of Trifolium Breeding In New Zealandmentioning
confidence: 99%